Pengembangan Media Bigbook Cerita Rakyat untuk Meningkatkan Empati dan Kemampuan Bercerita Anak Usia Dini - Dheasari, Agustiarini Eka (Universitas Muhammadiyah Magelang, 2020)
The purpose of this research is to develop bigbook folklore media to improve the empathy and storytelling ability of early childhood, especially age 5-6 years. This research is research and development (R&D) using ADDIE development model (Analyze, Design, Develop, Implementation, and Evaluate). Collecting data used interview guides, validation, observation sheets and teacher questionnaires. Data analysis techniques in this study used Independent t-test with a significance level of 0.05. Based on the results of the assessment experts showed that the product developed